Powdered Green Tea (Matcha) Attenuates the Cognitive Dysfunction via the Regulation of Systemic Inflammation in Chronic PM2.5-Exposed BALB/c Mice - Jong Min Kim; Jin Yong Kang; Seon Kyeong Park; Jong Hyun Moon; Min Ji Kim; Hyo Lim Lee; Hye Rin Jeong; Jong Cheol Kim; Ho Jin Heo (Antioxidants, 2021)
This study was conducted to evaluate the anti-amnesic effect of the aqueous extract of powdered green tea (matcha) (EM) in particulate matter (PM)2.5-induced systemic inflammation in BALB/c mice. EM ameliorated spatial learning and memory function, short-term memory function, and long-term learning and memory function in PM2.5-induced mice. EM protected against antioxidant deficit in pulmonary, dermal, and cerebral tissues. In addition, EM improved the cholinergic system through the regulation of acetylcholine (ACh) levels and acetylcholinesterase (AChE) activity in brain tissue, and it protected mitochondrial dysfunction by regulating the production of reactive oxygen species (ROS), mitochondrial membrane potential (MMP) and ATP contents in brain tissue. EM attenuated systemic inflammation and apoptotic signaling in pulmonary, dermal, olfactory bulb, and hippocampal tissues. Moreover, EM suppressed neuronal cytotoxicity and cholinergic dysfunction in hippocampal tissue. This study suggests that EM might be a potential substance to improve PM2.5-induced cognitive dysfunction via the regulation of systemic inflammation.